Utilisation of industrial waste (Fly ash) in synthesis of copper based surface composite through friction stir processing route for wear applications. (20th September 2018) - Kumar, Harikishor; Prasad, R.; Srivastava, A.; Vashista, M.; Khan, M.Z.
Abstract: Fly ash (FA), the solid waste resulting from combustion of coal in thermal power plants is a by-product produced in massive quantities across the world. It is considered as an environmental pollutant. Owing to its bad effects on the environment, research is being conducted all over the world for the utilisation of FA. The present work emphasizes the utilisation of FA as reinforcement in coppe rbased surface composite fabricated by friction stir processing (FSP). The properties of fabricated composite and its environmental impact through leaching test have also been reported in the present study. A groove of known dimension was machined at the centre of the plate (6 mm thickness) for compaction of the high amount of FA (almost 18 vol %), processed by FSP. The microstructural features of the fabricated composite were observed by optical and scanning electron microscope revealed equiaxed and fine grain structure with no concentration gradient, agglomeration and segregation along the grain boundary. The stir zone (SZ) was engulfed with particulate along with clean interface and excellent bonding. The XRD pattern revealed no intermetallics or in situ products except copper and particulate. Vickers microhardness tester machine adjudged significant improvement in hardness. The composite showed higher tensile strength and lower ductility as compared to copper. Enhancement in oxidation and corrosion resistance was also observed whereas electrical conductivity decreased as evaluated by four probe method. The pin on plate unidirectional dry sliding wear test was performed to evaluate the wear loss. The wear resistance of the fabricated composite improved substantially. The worn surface was observed by scanning electron microscope to have a detailed understanding of wear mechanism. Further through leaching test, it was observed that concentration of leached out metals was far below as specified in Indian legislation. Highlights: FA utilisation as reinforcement in Cu/FA surface composite fabricated by FSP. Homogeneous distribution of FA particles in copper matrix with excellent bonding. FA influenced mechanical, wear, electrical and oxidation and corrosion behaviour. Environmental impact of FA and Cu/FA composite through leaching test.